Using citizen science to engage the public in monitoring workplace breastfeeding support in Australia. (25th March 2021) - Rowbotham, Samantha; Marks, Leah; Tawia, Susan; Woolley, Emma; Rooney, Janelle; Kiggins, Elissa; Healey, Danielle; Wardle, Karen; Campbell, Vanessa; Bridges, Nicole; Hawe, Penelope
Abstract: Issue addressed: Returning to work is a major barrier to continued breastfeeding. While many large organisations in Australia have policies to support breastfeeding and expressing at work, it is not known how these are implemented in practice, what support is available in smaller workplaces or to what extent workplace support meets the needs of breastfeeding mothers. Methods: This pilot study trialled a citizen science approach where members of the public provided photographs and descriptions of breastfeeding facilities and support within their workplaces. The study was promoted through community networks and social media, and data were submitted via an online survey. Data were analysed inductively to identify key themes. Results: Thirty‐seven participants provided data on breastfeeding support in their workplace. Three key themes were identified: physical features and facilities; workplace culture; and organisational and occupational characteristics. There was considerable variation in workplace support and around half of the participants indicated that they had to use communal, poorly equipped and/or unhygienic spaces to breastfeed or express at work. Conclusion: While some employers have taken important steps towards supporting mothers to combine breastfeeding and work, there is room for improvement. Through this pilot study, we have demonstrated the feasibility and value of using a citizen science approach to obtain data from a range of workplaces along with perceptions of workplace characteristics that support or hinder breastfeeding and expressing at work. So what?: Citizen science is a useful approach to capturing data on workplace support for breastfeeding and could be scaled up to enable ongoing monitoring. The findings raise important issues around the interpretation and implementation of current legislation to support mothers in the workplace.